Genetic Analysis of the Hsm3 Protein Function in Yeast Saccharomyces cerevisiae NuB4 Complex - Evstyukhina, Tatiyana A. (Genes (Basel), 2021)
In the nuclear compartment of yeast, NuB4 core complex consists of three proteins, Hat1, Hat2, and Hif1, and interacts with a number of other factors. In particular, it was shown that NuB4 complex physically interacts with Hsm3p. Early we demonstrated that the gene HSM3 participates in the control of replicative and reparative spontaneous mutagenesis, and that hsm3Δ mutants increase the frequency of mutations induced by different mutagens. It was previously believed that the HSM3 gene controlled only some minor repair processes in the cell, but later it was suggested that it had a chaperone function with its participation in proteasome assembly. In this work, we analyzed the properties of three hsm3Δ, hif1Δ, and hat1Δ mutants. The results obtained showed that the Hsm3 protein may be a functional subunit of NuB4 complex. It has been shown that hsm3- and hif1-dependent UV-induced mutagenesis is completely suppressed by inactivation of the Polη polymerase. We showed a significant role of Polη for hsm3-dependent mutagenesis at non-bipyrimidine sites (NBP sites). The efficiency of expression of RNR (RiboNucleotid Reducase) genes after UV irradiation in hsm3Δ and hif1Δ mutants was several times lower than in wild-type cells. Thus, we have presented evidence that significant increase in the dNTP levels suppress hsm3- and hif1-dependent mutagenesis and Polη is responsible for hsm3- and hif1-dependent mutagenesis.